1999
DOI: 10.1210/endo.140.8.6913
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Dihydrotestosterone Differentially Masculinizes Tonic and Surge Modes of Luteinizing Hormone Secretion in Sheep*

Abstract: The control of LH secretion in sheep is sexually differentiated. Males begin to reduce their sensitivity to inhibitory steroid feedback, leading to a pubertal increase in tonic LH secretion by 10 weeks of age, but females remain hypersensitive until 30 weeks. Moreover, only females can respond to the positive feedback action of estradiol to produce a preovulatory LH surge. Prenatal exposure of the female lamb to testosterone masculinizes tonic LH and abolishes the LH surge postnatally. However, the type of ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
21
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 36 publications
6
21
0
Order By: Relevance
“…The present results suggest that prenatal AR activation in the female rat can prevent release of gonadotropin surges in adulthood, as has previously been shown in female sheep [48][49][50][51] and female monkeys [52]. These findings do not exclude the possibility that ER activation, consequent to the aromatization of T, may also normally play a role in the masculinzation of the gonadotropin surge induction mechanism.…”
Section: Discussionsupporting
confidence: 54%
“…The present results suggest that prenatal AR activation in the female rat can prevent release of gonadotropin surges in adulthood, as has previously been shown in female sheep [48][49][50][51] and female monkeys [52]. These findings do not exclude the possibility that ER activation, consequent to the aromatization of T, may also normally play a role in the masculinzation of the gonadotropin surge induction mechanism.…”
Section: Discussionsupporting
confidence: 54%
“…A recent study by Masek et al [12] suggests that aromatization of prenatal T mediates differentiation of the surge control of LH from operating in male sheep, because exposure of fetal ewes to T, but not to the nonaromatizable androgen DHT, blocks the LH surge response to estrogen priming. In contrast, both T and DHT treatment advances the pubertal rise in LH, suggesting that the tonic mode of gonadotropin secretion is masculinized by androgen.…”
Section: Discussionmentioning
confidence: 99%
“…The aromatization hypothesis was originally developed through research with rats and other short-gestation species, in which sexual differentiation occurs largely during the early postnatal period. Recent indirect evidence suggests that this mechanism may also apply to the sheep, an animal with a long gestation, in which masculinization occurs prenatally [12]. However, to our knowledge, it has never been demonstrated that the brain of the fetal sheep can aromatize androgens to estrogens.…”
Section: Introductionmentioning
confidence: 99%
“…The mean assay sensitivity was 0.78 ng/ml. An LH surge was determined to have occurred if hormone values exceeded twice the average baseline concentration for a minimum of 6 h [19]. The time of onset of the LH surges, the peak LH concentrations, and time of the LH peak were compared among the groups using a one-way ANOVA.…”
Section: Determination Of Circulating Lh and P Concentrationsmentioning
confidence: 99%